Mathematical Approach to Optimizing the Panchromatic Absorption of Natural Dye Combinations for Dye-Sensitized Solar Cells - Noah B. Manz; Paul A. Fuierer (Colorants, 2023)
The goal of this work was to optimize the combination of natural dyes producing panchromatic absorption matched to the AM1.5 solar spectrum for use in dye sensitized solar cells (DSSCs). Six classes of dyes (Anthocyanins, Betalins, Chlorophyll, Xanthonoids, Curcuminoids and Phycobilins) were explored. UV-Vis data and radial basis function interpolation were used to model the absorbance of 2568 combinations, and three objective functions determined the most commensurable spectrum. TiO2 anodes were sensitized with 42 dye combinations and IV measurements made on simple cells. The absorbance-optimized combination yielded an efficiency of only 0.41%, compared to 1.31% for a simple 1:1 molar ratio of Curcuminoids and α-Mangostin, which showed symbiotic effects. Our results indicate that panchromatic absorption alone is not sufficient to predict optimal DSSC performance, although the mathematical approach may have broader application.